A Study of the Furocoumarin Derivative of Ruta Chalepensis L. (Rutaceae) - Ekbal H.AL-Khateeb; Ali A. AL-Shamma; Bajes A. Nehar (College of Pharmacy University of Baghdad, 2017)
The content of Furocoumarin derivatives (Psoralens) of Ruta Chalepensis L. (Whole plant) was studied by simple extraction with petroleum ether (b.p. 60-80Co). The results indicated that the plant contains a total of about (0.015%).        Investigation of these compounds by thin layer chromatography (TLC) revealed the presence of at least four compounds of which methoxsalen (8-methoxypsoralen) was isolated.     It was identified and authenticated with a standard by spectral method, IR, NMR, Mass spectra and HPLC.This plant could be considered as a good source for supplying this compound, which is widely used in dermatological preparations.